1994
DOI: 10.1520/jfs13585j
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Analysis of Low Molecular Weight Alcohols and Acetone from Fire Debris Using Passive Headspace Concentration

Abstract: Passive headspace concentration was utilized for recovering methanol, ethanol, isopropanol and acetone from materials commonly found in fire debris. Gas Chromatography/Flame Ionization Detection was used for screening the extracts, followed by Gas Chromatography/Ion Trap Detection to confirm the presence of an alcohol or acetone with mass spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Currently, one of the most popular methods for isolating ILR from fire debris is passive adsorption onto an activated charcoal strip followed by solvent elution of the ILR using carbon disulfide, pentane, or another appropriate solvent. The performance of this technique has been well studied (1–4) and its procedures have been standardized (5).…”
mentioning
confidence: 99%
“…Currently, one of the most popular methods for isolating ILR from fire debris is passive adsorption onto an activated charcoal strip followed by solvent elution of the ILR using carbon disulfide, pentane, or another appropriate solvent. The performance of this technique has been well studied (1–4) and its procedures have been standardized (5).…”
mentioning
confidence: 99%
“…Identification of E85, however, may require slight modifications to those instrumental conditions to detect the ethanol if a traditional solvent delay is used. Phelps, Chasteen and Render showed that ethanol and other volatile oxygenated compounds could be extracted and identified using passive headspace concentration (8). To date, limited work has been done in the forensic field regarding E85.…”
mentioning
confidence: 99%